Microbiota Diversity in Non-Small Cell Lung Cancer Gut and Mouth Cavity Microbiota Diversity in Non-Small Cell Lung Cancer Patients - Brisudová, Aneta; Bielniková-Kryštofová, Hana; Motyka, Oldřich; Fritzová, Dominika; Katuchová, Vladimíra; Ponikelská, Natálie; Skanderová, Daniela; Raclavský, Vladislav; Michálek, Jaroslav; Mitták, Marcel; Švecová, Petra; Jakubec, Petr; et al. (Polish journal of microbiology, 2023)
Lung malignancies have a substantial impact on cancer incidence and mortality worldwide. Even though many factors involved in the development of the disease are known, many questions remain unanswered. Previous studies suggest that the intestinal microbiota may have a role in developing malignant diseases. According to some findings, the microbiota has proven to be a key modulator of carcinogenic processes and the immune response against cancer cells, potentially influencing the effectiveness of immunotherapy. In our study, we characterized culturable microorganisms associated with non-small cell lung cancer (NSCLC) that can be recovered from rectal swabs and mouthwash. In addition, we also explored differences in the culturable microbiota with two main types of NSCLC - adenocarcinoma (ADC) and squamous cell carcinoma (SCC). With 141 patients included in the study (86 ADC and 55 SCC cases), a significant difference was observed between the two types in seven bacterial species (Collinsella, Corynebacterium, Klebsiella, Lactobacillus, Neisseria, Rothia, and Streptococcus), including the site of origin. The relationship between microbial dysbiosis and lung cancer is poorly understood; future research could shed light on the links between gut microbiota and lung cancer development.
Keywords: mikrobiota; non-small cell lung carcinoma; microbiota; oncogenic mutations; nádory plic; nemalobuněčný karcinom plic; spinocelulární karcinom; adenokarcinom; Humans; lung cancer; Carcinoma, Squamous Cell; Adenocarcinoma; Microbiota; Lung Neoplasms; Carcinoma, Non-Small-Cell Lung; lidé